Molecular phylogeny and morphology of amphisphaeria (= lepteutypa) (amphisphaeriaceae) - Milan C. Samarakoon (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Amphisphaeriaceous taxa (fungi) are saprobes on decaying wood in terrestrial, mangrove, and freshwater habitats. The generic boundaries of the family have traditionally been based on morphology, and the delimitation of genera has always been challenging. Amphisphaeria species have clypeate ascomata and 1-septate ascospores and a coelomycetous asexual morph. Lepteutypa is different from Amphisphaeria in having eutypoid stromata and more than 1-septate ascospores. These main characters have been used for segregation of Lepteutypa from Amphisphaeria for a long time. However, the above characters are overlapping among Amphisphaeria and Lepteutypa species. Therefore, here we synonymized Lepteutypa under Amphisphaeria based on holomorphic morphology and multigene phylogeny. Further, our cluster analysis reveals the relationship between seven morphological traits among Amphisphaeria/Lepteutypa species and suggests those morphologies are not specific to either genus. Three new species (i.e., Amphisphaeria camelliae, A. curvaticonidia, and A. micheliae) are introduced based on morphology and LSU-ITS-RPB2-TUB2 phylogenies. Furthermore, the monotypic genus Trochilispora, which had been accepted in Amphisphaeriaceae, is revisited and synonymized under Hymenopleella and placed in Sporocadaceae.